2020
DOI: 10.1089/jmf.2019.4670
|View full text |Cite
|
Sign up to set email alerts
|

Plumbagin Suppresses Pulmonary Fibrosis via Inhibition of p300 Histone Acetyltransferase Activity

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic fibrosing interstitial lung disease with a poor prognosis similar to that of malignancy. The causes of IPF are not clearly known, and there is no effective therapy to date. In this study, the natural compound plumbagin, which was isolated from Plumbago rosea root extract, was screened for p300 inhibitory activity. Plumbagin specifically inhibited the activity of p300 toward histone acetyltransferases. Plumbagin treatment significantly suppressed transforming gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…50 Similarly, plumbagin, which was shown to be an inhibitor of p300, suppresses fibrosis in an idiopathic pulmonary fibrosis model. 51 However, these data do not support a role of steroids, specifically triamcinolone, in counterregulating the effects of TGF-b1 by impacting the histone epigenome. In fact, although the role of triamcinolone as an antifibrotic agent has been recognized for decades, a fully detailed mechanism underlying this widely accepted effect remains elusive.…”
Section: Discussionmentioning
confidence: 90%
“…50 Similarly, plumbagin, which was shown to be an inhibitor of p300, suppresses fibrosis in an idiopathic pulmonary fibrosis model. 51 However, these data do not support a role of steroids, specifically triamcinolone, in counterregulating the effects of TGF-b1 by impacting the histone epigenome. In fact, although the role of triamcinolone as an antifibrotic agent has been recognized for decades, a fully detailed mechanism underlying this widely accepted effect remains elusive.…”
Section: Discussionmentioning
confidence: 90%
“…PLB has a pleiotropic effect on various cellular functions. Some studies have reported that PLB displays anti-fibrotic properties in the lung, kidney and liver [ 23 , 25 , 32 ]. In this study, our data showed that PLB regulated tissue repair and collagen deposition in TS rats.…”
Section: Discussionmentioning
confidence: 99%
“…Nylon brush was used to brush the inner wall of the trachea back-and-forth for 8 times from tracheostoma to the distal trachea (about 1 cm length), and then the tracheal incision was sutured in the rats of Group (2), (3) and (4) to establish TS model. In Group (4), the rats were intraperitoneally injected with 4 mg/kg/d PLB for five consecutive days (refer to previous literature) [ 23 , 27 ]. PLB (20 mg) was dissolved in 20 μl DMSO first, then diluted in 50 ml normal saline at a final concentration of 0.4 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9]18 Studies have revealed that the level of serum albumin is inversely linked with Aβ deposition and Aβ positivity. 19 Research reports have also shown that Aβ [25][26][27][28][29][30][31][32][33][34][35] can induce in vitro cross-seeding of BSA, resulting in aggregates that were toxic to microglial cells. 20 Moreover, D-ribosemediated glycation of BSA is known to trigger its rapid amyloid formation that generates neurotoxic aggregates.…”
Section: ■ Introductionmentioning
confidence: 99%